Length weight relationship and size distribution long shells bakalang (Marcia hiantina Lamarck) in the coastal waters of Labakkang, Pangkep Regency - Hamsiah, Hamsiah; Asmidar, Asmidar; Hasrun, Hasrun; Kasmawati, Kasmawati (Hasanuddin University, 2018)
Seagrass ecosystems in the coastal Labakkang Pangkep regency is the habitat of various types of shellfish which is the target of local fishermen catch. One of the many species of shellfish found in this coastal area is the mussel shell (Marcia hiantina L.). This study aims to determine the relationship between the length and weight of the long shell size of mussel shells (Marcia hiantina L.) in the coastal waters catchment of Labakkang. This research was conducted in catching area at three locations in coastal waters of Labakkang based on density of seagrass and population with sampling every month from August 2014 until July 2015 by using descriptive method that is random sampling by measuring the length of shell and weight of each shellfish. The results showed that the constant value (b) of mussel shell (Marcia hiantina L.) in all observation stations ranged from 2,44 to 2,63, meaning growth pattern including negative allometrik means shell length growth faster than body weight with coefficient of determination (R2) ranging from 0,88 to 0,91 means to have a high enough. The distribution of the size of the mussel (Marcia hiantina L.) is found on the smallest C size station with the range 1,50 – 1,88 cm and the middle value of 1,69 cm and the largest with a range of 5,34 - 5,72 cm and the middle value of 5.53 cm.Keywords: Bakalang shell, Length weight, Coastal waters of Labakkang, Allometric negative